Dual Role of Triptolide in Interrupting the NLRP3 Inflammasome Pathway to Attenuate Cardiac Fibrosis - Pan, Xi-Chun; Liu, Ya; Cen, Yan-Yan; Xiong, Ya-Lan; Li, Jing-Mei; Ding, Yuan-Yuan; Tong, Yang-Fei; Liu, Tao; Chen, Xiao-Hong; Zhang, Hai-Gang (International journal of molecular sciences, 2019)
In a previous paper, we reported that triptolide (TP), a commonly used immunomodulator, could attenuate cardiac hypertrophy. This present study aimed to further explore the inhibition of cardiac fibrosis by TP and the possible mechanism from the perspective of the NOD-like receptor protein 3 (NLRP3) inflammasome. Hematoxylin-eosin and Masson’s staining, immunohistochemistry, and immunofluorescence were performed to observe cardiac fibrotic changes in mice and mouse cardiac fibroblasts (CFs). The Western blot, colocalization, and immunoprecipitation were applied to detect protein expression and interactions. Results suggested that TP dose-dependently inhibited cardiac fibrosis induced by isoproterenol and collagen production of CFs induced by angiotensin II. TP exhibited an antifibrotic effect via inhibiting activation of the NLRP3 inflammasome, which sequentially decreased IL-1β maturation, myeloid differentiation factor 88 (MyD88)-related phosphorylation of c-Jun N-terminal kinase (JNK), extracellular regulated protein kinase 1/2 (ERK1/2), and TGF-β1/Smad signaling, and ultimately resulted in less collagen production. Moreover, TP showed no antifibrotic effect in Nlrp3-knockout CFs. Notably, TP inhibited the expression of NLRP3 and apoptosis-associated speck-like proteins containing a caspase recruitment domain (ASC) as well as inflammasome assembly, by interrupting the NLRP3-ASC interaction to inhibit inflammasome activation. Finally, TP indeed inhibited the NLRP3-TGFβ1-Smad pathway in vivo. Conclusively, TP was found to play a dual role in interrupting the activation of the NLRP3 inflammasome to attenuate cardiac fibrosis.